Decisions, values and groups Reports from the ... Interdisciplinary Conference - United States. Air Force; Behavioral Sciences Division; Office of Scientific Research; Interdisciplinary Research Conference (1st : 1957 : University of Mexico). (New York Symposium Publications Division, Pergamon Press, 1960)
Annual.
Imprint varies: 1957, New York : Symposium Publications Division, Pergamon Press; 1958- , New York : Macmillan Co.
Sponsored by: 1957- , the U.S. Air Force, Office of Scientific Research, Behavioral Sciences Division.
Subtitle varies.
Keywords: Social psychology -- Congresses; Decision-making -- Mathematical models -- Congresses; Difference (Psychology) -- Congresses; Human behavior -- Congresses